Religio-centric Product Strategic: Halal Literacy and Brand Management Capabilities Towards Business Performance - Achmad Daengs Gatot Soeherman; Roymon Panjaitan (Jurnal Siasat Bisnis, 2023)
Purpose – This study aims to explore a new model concept finding that can bridge the research gap of halal literacy relationships, brand management skills that are centralized to religio-centric product strategies and the commitment to diversity as a function of moderation. Design/methodology/approach – Quantitative methods were used to collect data from a total of 186 respondents with PLS-SEM, instruments used with questionnaires and interviews taken randomly from a population of 320 spread across the island of Java. Findings – This concept is a novelty in efforts to improve business performance based on the religious nature of centrists in determining product strategies. Furthermore, the growth of product brand innovation is increasingly dynamic, demanding the participation of religion in leading competitive brands and the dissemination of halal literacy Research limitations/implications – In the meantime, in-depth research has not yet been carried out on other dimensions of the function of the previous variable religio-centric product strategy, such as halal marketing innovation capabilities and information technology configuration of halal product literacy. Practical implications – the application of a religion-centred marketing strategy is the company's ability to provide innovation in product strategy decisions that are committed to religious values and can be leveraged in current market understanding and future market forecasts. For stakeholders, this is a new faith-based business opportunity that can open up new segments in heterogeneous market demands. Originality/value – To contribute ideas for knowledge about religious-product strategies and the ability of MSME businesses to spread the importance of halal brand products to customers and through attention on innovation strategies of customer religiosity product needs that are oriented to the needs of halal products customers.